1970
DOI: 10.1126/science.167.3922.1252
|View full text |Cite
|
Sign up to set email alerts
|

Neuroglia: Gliosis and Focal Epilepsy

Abstract: Normal neuroglial cells buffer the extracellular space around neurons and presynaptic terminals against increases in potassium ions. Epileptic foci resulting from brain injury are characterized by areas of intense fibrillary gliosis bordering neuronal tissue. The known pathological changes that occur in gliosis may impair glial control of extracellular potassium ions and lead to excessively excitable neuronal border regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0
1

Year Published

1970
1970
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(61 citation statements)
references
References 12 publications
2
58
0
1
Order By: Relevance
“…In late 1940s Penfield and co workers established that glial scar is a irritable source for the focal seizures, which develop either by anoxic or traumatic brain damage [16]. One patient in the present research had post gliotic seizures due to traumatic gliotic scar in the brain.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In late 1940s Penfield and co workers established that glial scar is a irritable source for the focal seizures, which develop either by anoxic or traumatic brain damage [16]. One patient in the present research had post gliotic seizures due to traumatic gliotic scar in the brain.…”
Section: Discussionmentioning
confidence: 62%
“…Fibrillary gliosis resulting from prior brain injury bordering the normal neuronal tissue can trigger epilepsy by impairing the homeostasis of extracellular potassium ions [16]. In late 1940s Penfield and co workers established that glial scar is a irritable source for the focal seizures, which develop either by anoxic or traumatic brain damage [16].…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors suggested that impaired glial regulation of extracellular potassium is important in the transition from the interictal to the ictal state (21)(22)(23)(24). More recently, evidence has accumulated that glia hold a role in neural information processing (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…2,3 The almost invariable presence of gliotic scars in chronic focal epilepsy has led many to suggest a physiological role for glia in the disease. [4][5][6] Early studies on the role of astrocytes in epilepsy carried out mostly on gliotic scars induced by topical application of chemicals such as alumina or cobalt to the cortex of animal brains are reviewed by Tiffany-Castiglioni and Castiglioni. 7 In conclusion to their review, the authors write that "astrocytes can hypothetically contribute to epileptogenesis by any of three routes: (1) the initiation of neuronal hyperactivity in previously normal neurons, (2) the promotion of epileptic bursting in abnormal neurons, and (3) the failure to neutralize and arrest neuronal hyperactivity."…”
Section: Introductionmentioning
confidence: 99%